2011
DOI: 10.1021/ma201063t
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide–Poly(6-methyl-ε-caprolactone)–Polylactide Thermoplastic Elastomers

Abstract: Amorphous ABA type block aliphatic polyesters can be useful as degradable and biorenewable thermoplastic elastomers. These materials can be prepared by sequential ringopening transesterification polymerization (ROTEP) reactions and can exhibit a range of physical properties and morphologies. In this work a set of amorphous polylactideÀpoly(6-methyl-ε-caprolactone)Àpolylactide aliphatic polyester ABA triblock copolymers were prepared by consecutive controlled ring-opening polymerizations. Ring-opening polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
154
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 55 publications
(103 reference statements)
7
154
0
Order By: Relevance
“…With the bioderived βMδVL in hand, we demonstrated that bulk ROTEP using an organocatalyst proceeds at room temperature to high conversion, yielding an amorphous polyester with T g = -51°C (26,28). Simple chain extension through reaction with lactide (LLA or LA) leads to P(L)LA-PβMδVL-P(L)LA triblock polymers that can be tuned to have mechanical properties ranging from stiff tough plastics to soft and highly extendible elastomers (Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…With the bioderived βMδVL in hand, we demonstrated that bulk ROTEP using an organocatalyst proceeds at room temperature to high conversion, yielding an amorphous polyester with T g = -51°C (26,28). Simple chain extension through reaction with lactide (LLA or LA) leads to P(L)LA-PβMδVL-P(L)LA triblock polymers that can be tuned to have mechanical properties ranging from stiff tough plastics to soft and highly extendible elastomers (Fig.…”
Section: Significancementioning
confidence: 99%
“…In this paper we address this challenge by combining the efficient bioproduction of β-methyl-δ-valerolactone with controlled polymerization techniques to produce economically viable block polymer materials with mechanical properties akin to commercially available thermoplastics and elastomers. offer exceptional mechanical properties (26,27). βMδVL can be generated by direct fermentation of glucose or through the production of the intermediate compound mevalonate.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Sample PLLA-PM-PLLA (13-33-13) displayed a strain at break of 765% with ultimate tensile strength of 19.5 MPa [51,52]. With 30 vol% of poly(6-methyl-ε-caprolactone) (PMCL) as the elastic block, 1880% strain at break was achieved with 10.2 MPa ultimate stress [53].…”
Section: Block Copolymers Synthesized By Ring-opening Transesteriicatmentioning
confidence: 99%
“…The dihydroxyl terminated polymer is then used as a macro-initiator for the subsequent ring-opening polymerization of lactide. A variety of polymers can be used as soft block [16,17,21,27,31,38,41], provided that they have a suitably low glass transition temperature, and that they can be obtained with proper terminal functional groups. Recently, the research focused on the development of fully biobased PLA-containing triblocks copolymers, by employing biorenewable soft blocks, such as amorphous polyhydroxyalkanoates [18,26], polymethide [28] and polyesters derived from castor oil [44].…”
mentioning
confidence: 99%